Effectiveness of Assessment in Law Enforcement Offenses of Narcotics Abusers - Alfarisi , Salman; Andini, Orin Gusta; Alfian (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to describe the implementation of Integrated Assessment and assess the effectiveness of the assessment of criminal acts of narcotics abuse. The research method used is normative research method, supported by field data and in-depth interviews with respondents and sources relevant to the research topic. The results showed that not all cases involving narcotics offenders were given assessment recommendations due to differences in perception among law enforcement, and the high cost of assessment. The implementation of the assessment of narcotics abusers has not been effective because its implementation has encountered various obstacles. This article recommends that a review of the legal basis for handling narcotics is needed to ensure legal certainty in the implementation of assessments and the need for the government to take a health approach in handling narcotics in Indonesia.